1996
DOI: 10.1111/j.1365-2621.1996.tb12205.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of Heat Transfer in Meat Patties During Single‐sided Pan‐frying

Abstract: Our objectives were to mathematically model heat transfer in meat patties during single-sided pan-frying without and with turn-over, using the finite element method. Moisture loss rate was determined and included in the model to account for evaporation loss. The model was validated by comparing predicted and experimental temperature profiles monitored at three axial positions during pan-frying (one side and turn-over) at 140 and 180ЊC. Moisture loss rate, cooking time, and crust formation were functions of pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 12 publications
1
42
0
Order By: Relevance
“…A predictive model to simulate drying or other water removal processes in cellular foods generally uses an effective diffusivity as a function of moisture content to describe the moisture migration. 1,2 Such an effective diffusivity is an average of all the resistive pathways and is completely empirical, specific to a process and food material. But for the purpose of modeling drying processes, effective diffusivities should be based on the properties of cellular structures in addition to the moisture content of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…A predictive model to simulate drying or other water removal processes in cellular foods generally uses an effective diffusivity as a function of moisture content to describe the moisture migration. 1,2 Such an effective diffusivity is an average of all the resistive pathways and is completely empirical, specific to a process and food material. But for the purpose of modeling drying processes, effective diffusivities should be based on the properties of cellular structures in addition to the moisture content of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Mangalassary et al (2004) also suggested that marbling (intramuscular fat content) and moisture movement could significantly contribute to lower RTI in thicker meat products. Marbling in meat adds to the insulating effect (Woodams and Nowrey, 1968;Mangalassary et al, 2004) while moisture movement results in a decrease in heat transfer, causing a delay in temperature increase, thereby decreasing RTI (Ikediala et al, 1996;Shilton, Mallikarjunan, and Sheridan, 2002).…”
Section: Rate Of Temperature Increasementioning
confidence: 99%
“…Pan et al (2000) reported the heat, water and fat transfer models for double-sided contact-heating of frozen and unfrozen patties. The Ikediala et al (1996) and Ateba and Mittal (1994b), respectively. These were validated using experimental data of heating patties with an initial temperature of À22°C.…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors affecting the heat and mass transfer in the patties during cooking, such as cooking temperature and time, and physical and thermal properties of the patties (Berry, 1996;Dagerskog, 1979aDagerskog, , 1979bIkediala, Correia, Fenton, & Ben-Abdallah, 1996). The heat and mass transfer processes during hamburger contact cooking are complicated phenomena.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation